Exploring the attitudes of young Vietnamese consumers towards the packaging of Korean cosmetic products - Nguyen, Khanh Linh (2022)
This thesis aimed to study consumer behavior towards Korean cosmetic packaging by analyzing the importance of visual packaging elements, brand name, and price, which affect consumers' perception and decision-making towards a product. In this paper, qualitative approaches were used to interpret the data from in-depth interviews with customers in order to explore the tendencies of young Vietnamese consumer behavior in Vietnam. Results from the study illustrated that, visual elements such as color and graphic design were claimed to grab consumers' attention and influence their behaviors towards a product. Meanwhile, brand name, informative element, and price impacted and affected consumers' final purchase decisions the most. Overall, these factors were considered especially crucial for young Vietnamese consumers than visual elements, size, or material elements since the purchase decision is made after the informative element, brand name, and price were examined. Moreover, other external factors such as social, cultural, and personal factors (e.g., health concerns, living environments, lifestyles) were also considered indirective factors affecting their using and purchasing habits towards Korean cosmetic packaging. However, the visual elements are still an essential factor since they are the elements that attract and grab the consumer's first attention when viewing a product. The current study's findings also underscore the importance of packaging as an effective marketing tool and a premise for product appraisal. Recommendations and suggestions for improving packaging design are made after that, based on the findings result of this study